SEARCH FOR SEISMIC DISCONTINUITIES IN THE LOWER MANTLE - Vinnik L.; Kato M.; Kawakatsu H. (My University, 2001)
Indications of lower mantle discontinuities have been debated for decades, but still little is known about their properties, and their origins are enigmatic. In our study broad-band recordings of deep events are examined for the presence of signals from the lower-mantle discontinuities with a novel technique. We deconvolve vertical component of the P-wave coda in the period range around 10s by the S waveform and stack many deconvolved traces with moveout time corrections. In synthetic seismograms for an earth model without lower mantle discontinuities, the strongest signal thus detected in the time window of interest is often s`410'P phase (generated as S and reflected as P from the `410km' discontinuity above the source). In actual seismograms there are other phases that can be interpreted as converted from S to P at discontinuities in the lower mantle beneath the seismic source. We summarize the results of processing the seismograms (1) of deep events in Sunda arc at seismograph stations in east Asia, (2) deep Kermadec-Fiji-Tonga events at the J-array and FREESIA networks in Japan and stations in east Asia, and (3) deep events in the northwest Pacific region (Mariana, Izu-Bonin and the Japan arc) recorded at stations in north America. In our data there are indications of discontinuities near 860-880, 1010-1120, 1170-1250 and 1670-1800km depths. The clearest signals are obtained from the discontinuity at a depth of 1200km. We argue that the `900', `1200' and `1700km' discontinuities are global, but laterally variable in both depth and strength. Seismic stratification of the lower mantle may have bearings on the patterns of subduction, as revealed by tomographic models.
Keywords: Lower mantle; Discontinuities